THE USE OF SLANG IN SPEECH SITUATIONS: CONTEXTUAL, PRAGMATIC, AND SOCIOLINGUISTIC DIMENSIONS - Gulnazkhon Alimova Yuldashaliyevna (International Journal of Literature and Language Studies, 2026)
This article investigates the role of slang as a functionally motivated and contextually conditioned stratum of natural language. While traditionally dismissed as a marker of informal or sub-standard speech, slang is reconsidered here as a sociolinguistically complex register that serves a range of communicative purposes, including identity construction, affective expression, in-group solidarity, and economy of discourse. Drawing on Dell Hymes’ (1972) SPEAKING model as a primary analytical framework, the article examines the situational parameters that govern slang’s distribution across formal, informal, and digitally mediated contexts. Empirical attitudinal data and corpus-based observations are used to map patterns of slang use and avoidance, with particular attention to the interplay between social relationships, communicative goals, and register choice. The article argues that a comprehensive understanding of slang requires moving beyond prescriptive judgments toward a descriptive sociopragmatic account that situates slang within the broader ecology of communicative competence.